A model for reconfiguration of territory: the eurocity Chaves-Verín and tourism cooperation in the alto Tamega - Xulio Pardellas De Blas, Carmen Padín Fabeiro (Boletín de la Asociación de Geógrafos Españoles, 2013)
Resumen